1981
DOI: 10.1080/00223980.1981.9915289
|View full text |Cite
|
Sign up to set email alerts
|

Contingency Management in the Treatment of Adolescent Alcohol Drinking Problems

Abstract: Three case studies demonstrated that social and monetary reinforcement for abstinence reduced the rate of excessive alcohol drinking in adolescents. The self-monitoring and extrinsic reinforcement procedures (ABA reversal design) resulted in complete abstinence in a 15-year-old boy with a 10-year history of excessive alcohol abuse and hospitalization for an alcohol-induced psychosis. In the cases of the 13-year-old and 15-year-old girls with extensive alcohol abuse histories, the behavioral interventions decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Relatively few CM studies have been conducted with adolescent substance abusers. An early case study of three adolescents with alcohol use problems demonstrated that the combination of monetary and social reinforcement was useful in reducing or eliminating alcohol use during the CM phase, but that alcohol use markedly increased for two of the three participants during the return to baseline condition 6 . Two studies have also found CM efficacious in reducing cigarette smoking in adolescents 7, 8 …”
Section: Introductionmentioning
confidence: 99%
“…Relatively few CM studies have been conducted with adolescent substance abusers. An early case study of three adolescents with alcohol use problems demonstrated that the combination of monetary and social reinforcement was useful in reducing or eliminating alcohol use during the CM phase, but that alcohol use markedly increased for two of the three participants during the return to baseline condition 6 . Two studies have also found CM efficacious in reducing cigarette smoking in adolescents 7, 8 …”
Section: Introductionmentioning
confidence: 99%